Discourse features of women’s language in the social media as influenced by formal education - Maria Harumi Indrayani; Risa Rumentha Simanjuntak (UPT Bahasa Universitas Tanjungpura, 2019)
This research has a purpose to find the ways women express themselves through written form in social media, relationship between educational backgrounds of women and their language choice, and the markers of the women’s discourse. This research uses qualitative method by doing stratified random sampling and giving questionnaires. The data is analyzed by analyzing participants’ language choice in social media post and formal education status, then finding the similarities and differences, analyzing the relation between participants’ formal education status and their language choice in social media post, and analyzing the markers of women’s discourse in social media. The results of this study found that some women uses coherence and cohesive consistently, while some women choose to have very casual writing style. This study confirms that women tendency to use more standard forms is more likely to be driven by their awareness of using proper language, rather than as a way of claiming such status (Holmes, 2008). Lastly, this study figured that women usually use intra-sentential code-switch more often and women’s tendency to be more sensitive is the caused why women used a lot of adjective words related to feelings.